The Oxford Vegetarian Study: an overview. - Appleby, P; Thorogood, M; Mann, J; Key, T (1999)
The Oxford Vegetarian Study is a prospective study of 6000 vegetarians and 5000 nonvegetarian control subjects recruited in the United Kingdom between 1980 and 1984. Cross-sectional analyses of study data showed that vegans had lower total- and LDL-cholesterol concentrations than did meat eaters; vegetarians and fish eaters had intermediate and similar values. Meat and cheese consumption were positively associated, and dietary fiber intake was inversely associated, with total-cholesterol concentration in both men and women. After 12 y of follow-up, all-cause mortality in the whole cohort was roughly half that in the population of England and Wales (standardized mortality ratio, 0.46; 95% CI, 0.42, 0.51). After adjusting for smoking, body mass index, and social class, death rates were lower in non-meat-eaters than in meat eaters for each of the mortality endpoints studied [relative risks and 95% CIs: 0.80 (0. 65, 0.99) for all causes of death, 0.72 (0.47, 1.10) for ischemic heart disease, and 0.61 (0.44, 0.84) for all malignant neoplasms]. Mortality from ischemic heart disease was also positively associated with estimated intakes of total animal fat, saturated animal fat, and dietary cholesterol. Other analyses showed that non-meat-eaters had only half the risk of meat eaters of requiring an emergency appendectomy, and that vegans in Britain may be at risk for iodine deficiency. Thus, the health of vegetarians in this study is generally good and compares favorably with that of the nonvegetarian control subjects. Larger studies are needed to examine rates of specific cancers and other diseases among vegetarians.